ANALISIS DISIPLIN KERJA GURU DI TK SE-KECAMATAN BANGKO KABUPATEN ROKAN HILIR - ', Rosidayanti; ', Zulkifli; ', Hukmi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract:This study has to determine disipline of teacher working in the subdistrict bangko area rokan hilir. Population in this research is all teacher in subdistrict bangko area rokan hilir as many 34 teachers. All the population sampled (saturated sampling). This type of reseach is descriptive with quantitative approach. The technique used was a questionner (questionnare). The results showed that the work discipline analysis kindergarten teacher in subdistrict bangko area rokan hilir is quite good with percentage 61,79 %. Intention is to work discipline teacher in kindergarten subdistrict bangko area rokan hilir of consciousness itself carry out his job, working in accordane with the guidance of the task, and comply with regulation is quite good. Thus the kindergarten teacher discipline all subdistrict bangko area rokan hilir needs to be increased again.Key Words: Analysis of labor discipline teachers